PROPOSAL FOR A TOOL FOR HEALTH SURVEILLANCE OF CARDIOVASCULAR DISEASES: SOCIAL DETERMINANTS, TERRITORY AND EXTENDED PREVENTION - Izabel Pezarini Jiacon, Milene; Karolina da Silva Pereira, Anna; Siqueira da Rocha Queiroz, Verônica; Cristina Vieira da Silva, Viviane; Ximenes Oliveira, Silvia; Barreto Pereira, Jéssica; Islândia Barbosa Dantas de Meneses, Uberlandia (Revista Gênero e Interdisciplinaridade, 2026)
Cardiovascular diseases (CVDs) remain the leading cause of mortality in Brazil, disproportionately affecting populations in situations of social vulnerability. This study aimed to propose a health surveillance tool focused on CVDs, based on the articulation between social determinants of health, territory, and expanded prevention. This is an integrative literature review, conducted between November 2023 and January 2024, searching the SciELO, PubMed, LILACS, and BDENF databases, as well as technical documents from national and international institutions. The critical analysis of the studies allowed the identification of two main categories: (1) social inequities and unequal distribution of CVDs in the territory and (2) weaknesses in care and surveillance during times of health crisis. It is concluded that health surveillance of CVDs requires technologies that integrate clinical, social, and territorial variables, promoting the planning of fairer, more contextualized, and more effective actions. The proposed tool could contribute to more equitable health practices and to transforming surveillance into an instrument of social justice.